- #1

A_Munk3y

- 72

- 0

**implicit differentiation help :) again!**

## Homework Statement

Use implicit differentiation

1) x/(y-x

^{2})=1

and

2) (y

^{2}-1)

^{3}=x

^{2}-y

## The Attempt at a Solution

1) x/(y-x

^{2})=1

=> [(y-x

^{2})(1)-(x)((1*dy/dx)-2x)]/[(y-x)

^{2}]

^{2}=0

=> y-x

^{2}-x(dy/dx)+2x

^{2}=[(y-x)

^{2}]

^{2}

I think I'm going to stop here because I'm pretty sure it's wrong so no reason to keep putting what i got. What am i doing wrong here?2) (y

^{2}-1)

^{3}=x

^{2}-y

=> 3(y

^{2}-1)

^{2}*(2y(dy/dx) = 2x-(dy/dx)

=> 3(y

^{2}-1)

^{2}*(2y(dy/dx))+(dy/dx) = 2x

Now here, i know the next step is

(dy/dx)(3(y

^{2}-1)

^{2}*(2y)+1)=2x

But i have no idea how i should get to this step. How did the dy/dx (the one that comes first) come out and where did the other dy/dx go (it became a 1??)

can anyone explain this to me?